Zmienność budowy petrograficznej w pokładach węgla brunatnego kopalni Turów - Sądel, Beata (My University, 2016)
This study investigated the variability of petrographic composition of lignite Turów deposit. Based on the profiles of lignite seam and data from literature were made lithotypes II Lusatian and III Ścinawa seams. It was found that in the analyzed seams occurs mainly xylo-detritic lignite. With the collected samples were carried out detailed petrographic analysis. Based on the results, the share of macerals in lithotypes, was calculated. The results are presented in tables and graphs. It has been found that the main component of lignite in Turów deposit is huminite group.

W niniejszej pracy zbadano zmienność petrograficzną w pokładach węgla brunatnego w złożu Turów. W oparciu o profile węgla i dane literaturowe wytypowano litotypy w pokładach II łużyckim i III ścinawskim. W badanym złożu dominuje węgiel ksylo-detrytowy. Dzięki pobranym próbkom bruzdowym została przeprowadzona szczegółowa analiza petrograficzna. Na podstawie wyników badań laboratoryjnych obliczono dokładny udział procentowy macerałów w poszczególnych litotypach węgla brunatnego. Wyniki zamieszczono w tabelach i na wykresach. Stwierdzono, że głównym składnikiem węgla w złożu Turów jest grupa huminitu.
Petrographic variability in the seams of lignite mine Turow
Keywords: złoże Turów; węgiel brunatny; petrografia; Turów deposit; lignite; petrography